Quick Start Guide to VHDL - LaMeres, Brock J. (Springer International Publishing : Imprint: Springer, 2019)
This textbook provides a starter's guide to VHDL. This book can be used in conjunction with a one-semester course in Digital Systems Design or on its own for designers who only need an introduction to the language. This book is designed to provide a bottoms-up approach to learning the VHDL language. This design supports a course in which foundational knowledge is covered before moving into advanced topics. However, this design also supports use as a reference manual. The author has designed the presentation with learning goals and assessment at its core. Each section addresses a specific learning outcome that the student should be able to "do" after its completion. The concept checks and exercise problems provide a rich set of assessment tools to measure student performance on each outcome. A comprehensive coverage of the basic capability of VHDL; Emphasizes examples from which students can learn: contains a solved example for nearly every section in the book; Includes more than 400 exercise problems, as well as concept check questions for each section, tied directly to specific learning outcomes.